The repair of full-thickness articular cartilage defect using intra-articular administration of N-acetyl-d-glucosamine in the rabbit knee: randomized controlled trial. Issue 1 (December 2015) - Chang, Nai-Jen; Lin, Yi-Ting; Lin, Chih-Chan; Wang, Hsueh-Chun; Hsu, Horng-Chaung; Yeh, Ming-Long
Abstract Background Although various alterative models of therapy are used for cartilage repair, no definite conclusion has been reached. Glucosamine (GlcN) is widely used as a nutritional supplement. However, the clinical- evidence-based outcome of GlcN administration remains controversial.N -acetyl-d -glucosamine (GlcNAc), a derivative of GlcN, shows chondroprotective activity and mediates the activation of articular chondrocytes. Therefore, we investigated the effect of intra-articular administration of GlcNAc in rabbits' knee joints with experimental full-thickness articular cartilage (FTAC) defects. Methods Twelve male adult New Zealand white rabbits, providing 24 knees, were used in this study. FTAC defects were created in the high-weight-bearing area of the medial femoral condyles of bilateral knees. All rabbits were randomly allocated to analysis at postsurgical week 4 or postsurgical week 12. In the week 4 group, rabbits' knees (six per group) were intra-articularly injected with normal saline or with GlcNAc twice per week for 3 weeks, beginning 1 week postoperatively. In the week 12 group, the rabbits' knees (six in each group) were intra-articularly injected with normal saline or with GlcNAc twice per week for 4 weeks, beginning 1 week postoperatively. Rabbits were sacrificed at 4 or 12 weeks after surgery for macroscopic, histological and radiological examinations of the knee joints. Results All rabbits had no systemic or local adverse effects. The saline and GlcNAc groups showed visible differences in healing of the FTAC defect at the end of testing. At week 4, the GlcNAc group had a higher level of collagen type II (COL II) and showed up-regulated production of transforming growth factor (TGF)-β2 and TGF-β3, suggesting the involvement of endogenous growth factors. At week 12, the GlcNAc group displayed formation of hyaline-like cartilage regeneration with mature chondrocytes (SOX9+), robust glycosaminoglycan (GAG) content, and positive COL II content in both the adjacent cartilage and reparative sites. However, the saline group demonstrated mainly fibrocartilage scar tissue, indicating COL I expression. Furthermore, the GlcNAc group had significantly higher bone volume per tissue volume and higher trabecular thickness than the saline group. Conclusions Intra-articular GlcNAc may promote the repair of experimental FTAC defects in the rabbit knee joint model.